Health Professionals' knowledge and practice on basic life support and its predicting factors in Ethiopia: Systematic review and meta-analysis. - Worku Necho Asferie; Demewoz Kefale; Amare Kassaw; Amare Simegn Ayele; Gedefaye Nibret; Yohannes Tesfahun; Habitamu Shimels Hailemeskel; Solomon Demis; Shegaw Zeleke; Tigabu Munye Aytenew (PLoS ONE, 2024)
Background Basic Life Support (BLS) is a sequence of care provided to patients who are experiencing respiratory arrest, cardiac arrest, or airway obstruction. Its main purpose is to maintain the airway, breathing, and circulation through CPR. This review aimed to estimate the pooled prevalence of Health Professionals' knowledge and practice on basic life support in Ethiopia. Method Eligible primary studies were accessed from international database (PubMed, Google Scholar, Hinari databases) and grey literatures found in online repositories. The required data were extracted from those studies and exported to Stata 17 for analysis. A weighted inverse-variance random-effects model and Der Simonian-Laird estimation method were used to compute the overall pooled prevalence of Health Professional's knowledge, practice of basic life support and its predictors. Variations across the included studies were checked using forest plot, funnel plot, I2 statistics, and Egger's test. Result A total of 5,258 Health Professionals were included from 11 studies. The pooled prevalence of knowledge and practice outcomes on basic life support in Ethiopia were 47.6 (95% CI: 29.899, 65.300, I2: 99.21%) and 44.42 (95% CI: 16.42, 72.41, I2: 99.69) respectively. Educational status of the Professional's was significantly associated with knowledge outcome. Those who had degree and above were 1.9 times (AOR: 1.90 (1.24, 2.56)) more likely knowledgeable on basic life support than under degree. Conclusion The overall pooled estimates of Health Professionals knowledge and practice on basic life support was considerably low. The educational status of the Health Professionals was significantly associated with knowledge outcome. The Health Professionals and responsible stakeholders should focus on the basic life support at Health Institutions. The professionals should advance their knowledge and skill on basic life support for the patients.